2020
DOI: 10.1021/acs.est.0c00958
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Additivity of Cytotoxicity Associated with Disinfection Byproducts in Potable Reuse and Conventional Drinking Waters

Abstract: Recent studies used the sum of the measured concentrations of individual disinfection byproducts (DBPs) weighted by their Chinese hamster ovary (CHO) cell cytotoxicity LC50 values to estimate the DBP-associated cytotoxicity of disinfected waters. This approach assumed that cytotoxicity was additive rather than synergistic or antagonistic. In this study, we evaluated whether this assumption was valid for mixtures containing DBPs at the concentration ratios measured in authentic disinfected waters. We examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 48 publications
5
107
1
1
Order By: Relevance
“…Although unregulated DBP classes (e.g. haloacetaldehydes and haloacetonitriles) occur at lower concentrations than regulated THMs and HAAs, they can contribute more to the cytotoxicity associated with disinfection byproducts than regulated THMs and HAAs in conventional drinking waters ( Lau et al., 2020 ). This lends further credence to the application of UV 254 screening during synoptic watershed sampling to understand potential DBP formation during drinking water treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Although unregulated DBP classes (e.g. haloacetaldehydes and haloacetonitriles) occur at lower concentrations than regulated THMs and HAAs, they can contribute more to the cytotoxicity associated with disinfection byproducts than regulated THMs and HAAs in conventional drinking waters ( Lau et al., 2020 ). This lends further credence to the application of UV 254 screening during synoptic watershed sampling to understand potential DBP formation during drinking water treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It is noted this toxicity calculation approach might be limited by not considering synergistic effects, differences between human and animal cells, and association with human health risk ( McKenna et al., 2019 ). Though Lau et al. (2020) validated using the sum of cytotoxic potency weighted DBP concentrations as an estimate of the CHO cell cytotoxicity associated with known DBPs in real disinfected waters, including potable reuse waters.…”
Section: Methodsmentioning
confidence: 99%
“…Ambient bromate, NDMA, THM4, and HAA5 were also measured and monitored throughout the treatment train to assess pre-oxidation implications on DBP formation. The study utilizes calculated cytotoxicity and genotoxicity quantities from methods reported elsewhere to identify and provide comparisons of the pre-oxidiation GAC treatment options ( Allard et al., 2015 ; Chuang and Mitch, 2017 ; Krasner et al., 2016 ; Lau et al., 2020 ; Plewa et al., 2017 ; Smith et al., 2010 ). Specifically, the toxic potencies of DBPs formed during formation potential experiments were calculated by normalizing measured concentrations to published cytotoxicity and genotoxicity lethal concentrations of individual DBPs ( Wagner and Plewa, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This gives the contribution of each DBP to the overall calculated toxicity and allows the prioritization of DBPs not only based on their concentrations but also their toxicity. It has recently been showed that the additivity of individual toxicities was representative of the CHO cell cytotoxicity associated with known DBPs in real disinfected waters [55]. Several studies reported the importance of Br-and/or I-DBPs over Cl-DBPs using this approach [55][56][57][58][59][60].…”
Section: The Detrimental Effects Of Halidementioning
confidence: 99%
“…It has recently been showed that the additivity of individual toxicities was representative of the CHO cell cytotoxicity associated with known DBPs in real disinfected waters [55]. Several studies reported the importance of Br-and/or I-DBPs over Cl-DBPs using this approach [55][56][57][58][59][60]. I-DBPs exhibiting particularly high toxicity, despite their usually much lower concentration in treated waters may be important toxicity drivers.…”
Section: The Detrimental Effects Of Halidementioning
confidence: 99%